Preservation of The People's Story Of Mandailing Natal as a Learning Source for Developing Character Values of Students - Sari Hasibuan, Nikmah; Afifah, Nur; Marlina Harahap, Eli; Andriany, Devi; ., Khairunnisa; Agustini, Rini (KnE Social Sciences, 2023)
This study aims to determine how the use of Mandailing Natal folklore as a learning resource for fostering the character values of students at SMP Muhammadiyah 29 Padangsidimpuan while preserving regional Mandailing Natal literature in the form of folklore. The research method used in this research is descriptive analytical method, which is a method that describes clearly the object under study, and describes the data as a whole, systematically, and accurately. Data collection in this study was carried out using observation, interviews, and documentation. Based on the results of this study, it can be concluded that the Mandailing Natal folklore can be used as a learning resource in developing students’ character values. After the use of the Mandailing Natal folklore as a source of learning Indonessian, it was evident that the students’ attitudes changed for the better. This can be seen from the percentage change in student attitudes after the use of the Mandailing Natal folklore to foster student character values in Indonesian language learning, namely good attitudes to very good, increased by 21% of the research sample, good attitudes remained good as much as 41%, attitude 24% good enough to be good, and 14% good enough attitude. Keywords: Character; student attitudes; mandailing Natal; Muhammadiyah